2017
DOI: 10.3389/fcimb.2017.00288
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Tick Cystatin OmC2 Targets Lysosomal Cathepsins S and C in Human Dendritic Cells

Abstract: To ensure successful feeding tick saliva contains a number of inhibitory proteins that interfere with the host immune response and help to create a permissive environment for pathogen transmission. Among the potential targets of the salivary cystatins are two host cysteine proteases, cathepsin S, which is essential for antigen- and invariant chain-processing, and cathepsin C (dipeptidyl peptidase 1, DPP1), which plays a critical role in processing and activation of the granule serine proteases. Here, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…In the soft tick Ornithodoros moubata, a cystatin was internalized by host dendritic cells and targeted cathepsin S and cathepsin C, affecting their maturation [77]. Cystatins from other tick species also have immunosuppressive functions [78][79][80]. Of the 12 cystatins identified in tick saliva from this study (S1B Fig, S1 Table), seven were secreted on or after 72 h of feeding, indicating that majority of cystatins might be involved in regulating tick feeding functions after the tick has initiated feeding.…”
Section: A) a Americanum Tick Saliva Contains A Large Diversity Of Pmentioning
confidence: 74%
“…In the soft tick Ornithodoros moubata, a cystatin was internalized by host dendritic cells and targeted cathepsin S and cathepsin C, affecting their maturation [77]. Cystatins from other tick species also have immunosuppressive functions [78][79][80]. Of the 12 cystatins identified in tick saliva from this study (S1B Fig, S1 Table), seven were secreted on or after 72 h of feeding, indicating that majority of cystatins might be involved in regulating tick feeding functions after the tick has initiated feeding.…”
Section: A) a Americanum Tick Saliva Contains A Large Diversity Of Pmentioning
confidence: 74%
“…Several researchers have reported cystatins in other tick species indicated that they play important roles in tick feeding physiology (72). In the soft tick Ornithodoros moubata, a cystatin was internalized by host dendritic cells and targeted cathepsin S and cathepsin C, affecting their maturation (73). Cystatins from other tick species also have immunosuppressive functions (7476).…”
Section: Resultsmentioning
confidence: 99%
“…The shortcomings of this method are that a lot of venom from the snakes is required to be collected and the relatively lower yield of the proteins, as well as the multiple steps. At present, the cystatins are usually expressed in the Pichia pastoris ( P. pastoris ) or insect cells probably due to the relatively complex structures, which might affect their expression and folding [13,16]. Actually, cystatins were usually expressed as inclusion bodies in the E. coli [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In bloodsucking animals, such as ticks, cystatins are usually expressed in their salivary glands or the midgut, which suggests that cystatins might participate in the feeding process of bloodsuckers [11,12,13,14,15]; while in snakes, the cystatins usually exist in their venom glands, which have been reported to suppress the growth, invasion, and metastasis of B16F10 cells and MHCC97H cells, as well as to inhibit tumor angiogenesis [16,17,18,19]. At present, more cystatins have been identified from venomous insects, snakes, fishes, or mollusks through gene cloning, and transcriptomic and proteomic approaches [20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%